(untitled) (Fractal: Journal of Psychology, 2009)
We objective to discuss dance in the context of the Psychiatric Reform, through the analysis of a corporal expression group of the Center for Psychosocial Care (CAPS). We followed some meetings and we interviewed some professionals involved with it. We also participated in a group meeting. We observed that this experience can function as a Psychiatric Reform tool that enables new ways of dealing with the difference, but it can be perceived by the manicomial logic as well. Besides, the group was a means of reflection on the service structure and on the need to create new forms of care.